A novel formula used for predicting hepatocellular carcinoma after the achievement of sustained virologic response by direct-acting antivirals in patients with chronic hepatitis C. - Yuji Yoshida; Masanori Atsukawa; Chisa Kondo; Michika Kitamura; Kaori Shioda-Koyano; Tadamichi Kawano; Hiroki Ono; Korenobu Hayama; Tomomi Okubo; Taeang Arai; Norio Itokawa; Katsuhiko Iwakiri (PLoS ONE, 2023)
Although eliminating HCV can prevent hepatocellular carcinoma (HCC), some patients develop HCC even after obtaining sustained virologic response (SVR). Previously, we developed a new formula to predict advanced liver fibrosis. This study aimed to clarify the usefulness of this formula for predicting HCC after achieving SVR. Among 351 consecutive patients who had been treated with direct-acting antivirals, 299 were included in this study. New formula scores were used as a marker for predicting liver fibrosis and as a predictive model for HCC incidence. The participants were 172 men and 127 women with a median age of 68 years. The median new formula score was -1.291. The cumulative HCC incidence rates were 4.3%, 9.7%, and 12.5% at 1, 3, and 5 years, respectively. The cumulative incidence of HCC was significantly higher in patients with a history of HCC than in those without treatment history of HCC (P = 2.52×10-26). Multivariate analysis revealed that male (HR = 6.584, 95% CI = 1.291-33.573, P = 0.023) and new formula score (HR = 1.741, 95% CI = 1.041-2.911, P = 0.035) were independent factors associated with the development of HCC in patients without a treatment history of HCC. The optimal cutoff value for predicting the development of HCC was -0.214. The cumulative incidence rates of HCC in patients with new formula scores ≥-0.214 were 5.4%, 15.3%, and 15.3% at 1, 3, and 5 years, respectively, whereas the incidence rates of HCC in patients with new formula scores <-0.214 were 0.0%, 0.6%, and 4.8%, respectively (P = 2.12×10-4). In conclusion, this study demonstrated the usefulness of new formula scores as a predictor of HCC after achieving SVR, especially in patients without past treatment history of treatment for HCC.